2009
DOI: 10.1523/jneurosci.5714-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

P2X4-Receptor-Mediated Synthesis and Release of Brain-Derived Neurotrophic Factor in Microglia Is Dependent on Calcium and p38-Mitogen-Activated Protein Kinase Activation

Abstract: Microglia in the dorsal horn of the spinal cord are increasingly recognized as being crucial in the pathogenesis of pain hypersensitivity after injury to a peripheral nerve. It is known that P2X4 purinoceptors (P2X4Rs) cause the release of brain-derived neurotrophic factor (BDNF) from microglia, which is necessary for maintaining pain hypersensitivity after nerve injury. However, there is a critical gap in understanding how activation of microglial P2X4Rs leads to the release of BDNF. Here, we show that stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
389
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(407 citation statements)
references
References 54 publications
18
389
0
Order By: Relevance
“…It was shown that activation of microglial P2X4Rs stimulates the synthesis and release of brain‐derived neurotrophic factor (BDNF)52, 57, and that BDNF then causes an alteration of transmembrane anion gradient in a subpopulation of dorsal horn lamina I neurons presumably through the downregulation of the neuronal chloride transporter, KCC2, which in turn renders γ‐aminobutyric acid and glycine effects depolarizing, rather than hyperpolarizing, in these neurons (Figure 3). Furthermore, Keller et al 58.…”
Section: Spinal Microglia Are Crucial For Neuropathic Painmentioning
confidence: 99%
“…It was shown that activation of microglial P2X4Rs stimulates the synthesis and release of brain‐derived neurotrophic factor (BDNF)52, 57, and that BDNF then causes an alteration of transmembrane anion gradient in a subpopulation of dorsal horn lamina I neurons presumably through the downregulation of the neuronal chloride transporter, KCC2, which in turn renders γ‐aminobutyric acid and glycine effects depolarizing, rather than hyperpolarizing, in these neurons (Figure 3). Furthermore, Keller et al 58.…”
Section: Spinal Microglia Are Crucial For Neuropathic Painmentioning
confidence: 99%
“…Activation of the P2X4 receptor leads eventually to the activation of p38 and release of BDNF [65,66]. Up-regulation of the P2X4 receptor in spinal cord microglia was later demonstrated to require the CCL21 chemokine, which is expressed only in damaged neurons [67], and turned out to be necessary for the development of nerve injury-induced tactile allodynia and, to a lesser extent, peripheral inflammation [68].…”
Section: Spinal Cord Microglia and Astrocytesmentioning
confidence: 99%
“…This increased expression appears to be specific since P2X4 receptor protein expression is not increased in neurons or astrocytes following trauma or injury [27,41]. Several intracellular signaling pathways have been implicated in the upregulation of P2X4 receptor expression including the PI3K/AKT pathway [42], and lyn kinase via an associated fibronectin/integrin mechanism [43][44][45][46][47][48][49].…”
Section: P2x4 Receptorsmentioning
confidence: 99%
“…This action appears to be mediated by increased intracellular Cl − concentrations in lamina I neurons that is dependent on brain-derived neurotrophic factor (BDNF) and neurotropin (TrkB) receptor signaling pathways [45,47]. P2X4 receptor stimulation results in down-stream signaling involving PIP2, PIP3, and p38 MAPK and subsequent release of BDNF [48,49]. Microglial P2X4 receptor stimulation also leads to phosphorylation of the NMDA receptor NR1 on subunit spinal neurons [45] that is likely mediated by P2X7-dependent release of interleukin-1β (IL-1β).…”
Section: P2x4 Receptorsmentioning
confidence: 99%
See 1 more Smart Citation